Marmara Üniversitesi Öğrencilerinde ve Öğretim Üyelerinde Sigara Alışkanlığı ve Durağan Maliyet İlişkisi - (:unkn) unknown (My University, 2012)
Geleceğin sağlık profesyonelleri olacak hekim, diş hekimi, eczacı, hemşire ve ebe adaylarının ve ilgili fakültelerdeki öğretim elemanlarının sigara içme alışkanlıkları ve nikotin bağımlılıklarının ölçülmesi, sigaranın öğrencilere ve öğretim elemanlarına durağan maliyetinin hesaplanması amaçlanmıştır. Çalışma kapsamına Marmara Üniversitesi Tıp, Diş Hekimliği, Eczacılık Fakülteleri ve Sağlık Bilimleri Fakültesi Hemşirelik- Ebelik Bölümü'ndeki öğrenciler ile öğretim elamanları dâhil edilmiştir. Veri toplama aracı olarak Fagerstrom nikotin bağımlılık testi (FNBT), sosyo-demografik ve maliyet ölçmeye yarayan sorular uygulanmıştır. Öğrencilerin %22'sinde ve öğretim elemanlarının %36,8'inde sigara alışkanlığı saptanmıştır. İki prevalans arasında anlamlı fark vardır (t=11,08; p<0,05). Öğrencilerin FNBT puanı ortalaması 4,1±1,9 iken öğretim üyelerinin FNBT puanı ortalaması 6,6±2,3 dur. Her iki ortalama arasında istatistiksel olarak anlamlı fark vardır (t=8,37; p<0,05). Yapılan hesaplamalara göre öğrenci yıllık gelirinin 1/4'ünü, öğretim elemanı ise 1/5'ini sigaraya ayırmaktadır. Bu çalışmada sadece durağan maliyet hesaplanmıştır; dolaylı maliyet hesaplanmamıştır. Sağlık alanında eğitim veren ve öğrencilere örnek olan öğretim elemanlarının sigara bırakmayı teşvik edici çalışmalara destek verebilmeleri için öncelikle kendilerinin sigarayı bırakmaları gereklidir.

It was aimed in this study to quantify smoking habits and nicotine dependency of future health care professionals such as doctors, dentists, pharmacists, nurses, and midwives, as well as academic members of associated faculties and to calculate the economic steady cost of smoking. Students in the faculties of Medicine, Dentistry, and Pharmacy, and Faculty of Health Sciences Department of Nursing and Midwifery and faculty members in Marmara University were included in the study. As a means of data collection, Fagerstrom test for nicotine dependence (FTND), and questionnaire including questions about socio-demographic data and cost of smoking were performed. Prevalence of smoking was found 36,89% for faculty members and 22,02% for students; there was significant diff erence between these two groups (t=11,08; p<0,05). Th e mean FTND score of the students and faculty members was 4,1±1,9, and 6,6±2,3, respectively. Th ere was also statistically significant diff erence between the mean FTND scores of two groups (t=8,37; p<0,05). According to calculations, students and faculty members spends 1/4 and 1/5 -of their income to smoking, respectively. Only steady costs were calculated in this study; indirect costs of smoking were not included. Teaching staff of health care education like a medicine, pharmacy, dentistry, nursing and midwifery in university need to quit smoking themselves in order to encourage smoking cessation. Th is study is unique for investigation smoking status students and trainers at the university level. Th is is also only survey that measures the cost of nicotine dependency and smoking. Academic staff s in field of health sciences should, as a role model, first quit smoking themselves to promote smoking cessation activities.
The Relation Between Smoking Habit Among the Students and Faculty Members in Marmara University and Steady Cost of Smoking
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel